Irradiation effects on antibody performance in the frame of biochip-based instruments development for space exploration. Issue 1 (26th January 2016) - Baqué, M.; Dobrijevic, M.; Le Postollec, A.; Moreau, T.; Faye, C.; Vigier, F.; Incerti, S.; Coussot, G.; Caron, J.; Vandenabeele-Trambouze, O.
Abstract: Several instruments based on immunoassay techniques have been proposed for life-detection experiments in the framework of planetary exploration but few experiments have been conducted so far to test the resistance of antibodies against cosmic ray particles. We present several irradiation experiments carried out on both grafted and free antibodies for different types of incident particles (protons, neutrons, electrons and 12 C) at different energies (between 9 MeV and 50 MeV) and different fluences. No loss of antibodies activity was detected for the whole set of experiments except when considering protons with energy between 20 and 30 MeV (on free and grafted antibodies) and fluences much greater than expected for a typical planetary mission to Mars for instance. Our results on grafted antibodies suggest that biochip-based instruments must be carefully designed according to the expected radiation environment for a given mission. In particular, a surface density of antibodies much larger than the expected proton fluence would prevent significant loss of antibodies activity and thus assuring a successful detection.